Two New Energetic Hexagonal Anti-Perovskites (N2H5)3X[B12H12] · H2O (X− = [NO3]− and [ClO4]−): Crystal Structure, Vibrational Spectra, and Thermal Decomposition - Rouzbeh Aghaei Hakkak; Thomas M. Klapötke; Thomas Schleid (Crystals, 2024)
Two novel energetic anti-perovskite compounds with the chemical formula (N2H5)3X[B12H12] · H2O, where X− is either [NO3]− or [ClO4]−, were successfully synthesized. Both dodecahydro-closo-dodecaborates crystallize orthorhombically in the space group Cmc21, exhibiting relatively similar lattice parameters ((N2H5)3[NO3][B12H12] · H2O: a = 915.94(5), b = 1817.45(9), c = 952.67(5) pm, (N2H5)3[ClO4][B12H12] · H2O: a = 1040.51(6), b = 1757.68(9), c = 942.34(5) pm both for Z = 4). Their synthesis involved a two-step process: first, Cs2[B12H12] passed through a cation exchange column to yield the acidic form of the dodecahydro-closo-dodecaborate, (H3O)2[B12H12]. This aqueous solution was subsequently neutralized with hydrazinium hydroxide and mixed with the corresponding water-dissolved hydrazinium salt (nitrate or perchlorate). Characterization of the obtained crystals was performed by single-crystal X-ray diffraction and Raman spectroscopy as well as thermal analyses (TG-DTA and DSC). The crystal structure determinations revealed that both compounds adopt a hexagonal anti-perovskite structure, distorted by the presence of water molecules. These compounds containing oxidizing oxoanions demonstrate a remarkable ability to release large amounts of energy (almost 2100 J/g) upon thermal decomposition.